Large and stable genome edits at the sorghum alpha kafirin locus result in changes in chromatin accessibility and globally increased expression of genes encoding lysine enrichment - Hurst, J. Preston; Yobi, Abou; Li, Aixia; Sato, Shirley; Clemente, Thomas E.; Angelovici, Ruthie; Holding, David R. (Frontiers in Plant Science, 2023)
Sorghum is a resilient and widely cultivated grain crop used for feed and food. However, the grain is deficient in lysine, an essential amino acid. This is due to the primary seed storage proteins, the alpha-kafirins, lacking lysine. It has been observed that reductions in alpha-kafirin protein results in rebalancing of the seed proteome and a corresponding increase in non-kafirin proteins which leads to increased lysine content. However, the mechanisms underlying proteome rebalancing are unclear. This study characterizes a previously developed gene edited sorghum line, with deletions at the alpha-kafirin locus. A single consensus guide RNA leads to tandem deletion of multiple members of the gene family in addition to the small target site mutations in remaining genes. RNA-seq and ATAC-seq were utilized to identify changes in gene expression and chromatin accessibility in developing kernels in the absence of most alpha-kafirin expression. Several differentially accessible chromatin regions and differentially expressed genes were identified. Additionally, several genes upregulated in edited sorghum were common with their syntenic orthologues differentially expressed in maize prolamin mutants. ATAC-seq showed enrichment of the binding motif for ZmOPAQUE 11, perhaps indicating the transcription factor’s involvement in the kernel response to reduced prolamins. Overall, this study provides a resource of genes and chromosomal regions which may be involved in sorghum’s response to reduced seed storage proteins and the process of proteome rebalancing.